Bypassing health facilities for childbirth: a multilevel study in three districts of Gujarat, India - Mariano Salazar; Kranti Vora; Ayesha De Costa (Taylor & Francis Group, 2016)
Background: Bypassing available facilities for childbirth has important implications for maternal health service delivery and human resources within a health system. The results are the additional expenses imposed on the woman and her family, as well as the inefficient use of health system resources. Bypassing often indicates a lack of confidence in the care provided by the facility nearest to the mother, which implies a level of dysfunctionality that the health system needs to address. Over the past decade, India has experienced a steep rise in the proportion of facility births. The initiation of programs promoting facility births resulted in a rise from 39% in 2005 to 85% in 2014. There have been no reports on bypassing facilities for childbirth from India. In the context of steeply rising facility births, it is important to quantify the occurrence of and study the relative contributions of maternal characteristics and facility functionality to bypassing. Objectives: 1) To determine the extent of bypassing health facilities for childbirth among rural mothers in three districts of Gujarat, India, 2) to identify associations between the functionality of an obstetric care (OC) facility and it being bypassed, and 3) to assess the relative contribution of maternal and facility characteristics to bypassing. Design: A cross-sectional survey of 166 public and private OC facilities reporting ≥30 births in the 3 months before the survey was conducted in three purposively selected districts (Dahod, Sabarkantha, and Surendranagar) in the state of Gujarat, India. Besides information on each facility, data from 946 women giving birth at these facilities were also gathered. Data were analyzed using a multilevel mixed-effects logistic regression model. Results: Off all mothers, 37.7% bypassed their nearest facility for childbirth. After adjusting for maternal characteristics, for every one-unit increase in the facility's emergency obstetric care (EmOC) signal functions, the odds of bypassing a facility for childbirth decreased by 37% (adjusted odds ratio [AOR] 0.63, 95% confidence interval [CI]: 0.53-0.76). Conclusions: This study shows that independent of maternal characteristics, in our setting, women will bypass obstetric facilities that are not adequately functional, and travel further to others that are more functional. It is important that the health system should focus on facility functionality, especially in the context of sharply rising hospital births.